The Utilization Of The Siwalima Museum As A History Learning Medium In Ambon City - Rosalia Santri; Kasman Renyaan; Rahma Temarwut (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2026)
History learning in schools is often considered monotonous because it is dominated by lecture methods and the use of textbooks, thus it is less able to build deep understanding among students. Therefore, more contextual and interactive learning media are needed, one of which is the utilization of museums as learning resources. This study aims to explore and explain the utilization of the Siwalima Museum as a medium for history learning for students in Ambon City. This research employs a descriptive qualitative method with data collection techniques including participatory observation, interviews, and literature study. The results show that the utilization of the Siwalima Museum by history teachers in Ambon City is able to create more active, contextual, and enjoyable learning, as students not only learn but also gain historical tourism experiences. Through direct observation of collections and historical objects, students are encouraged to explore historical sources independently as well as in groups. The use of the museum also promotes a shift in history learning strategies from passive to active, which is reflected in increased enthusiasm, curiosity, and student involvement in understanding and relating historical information to present-day life. In addition, learning in the museum contributes to the development of critical thinking skills, independent learning, group collaboration, as well as skills in observing and analyzing artifact-based historical sources. Visual and concrete learning experiences deepen students’ understanding while fostering an appreciation of cultural heritage and developing historical awareness.